E-MARKETING FOR BANKING SERVICES IS A WAY TO REACH THE GOLDEN SUMMIT: ASSYRIA BANK IS AN EXAMPLE - Adel Nashaat Muhammad Al-Hassani (Scholar Express Journals, 2024)
This study aimed to measure the extent of electronic marketing’s awareness of the banking services of Assyria Bank and its role in reaching the golden summit by focusing on the accompanying electronic banking services as a field of modern marketing knowledge, given the high standardization of banking services in their content. Banking management must look for other means and methods through which it can compete and obtain better results. If it is difficult for banking service to be, in its essence, one of the areas of competition and to highlight the golden or relative summit, then the quality of this service and the method of providing it may be the only area of competition. All of Assyria Banks were studied using a comprehensive survey method . The researcher concluded that the majority of the research sample’s opinions depend on their own websites on the Internet to introduce themselves and their affiliated branches, in addition to introducing customers to their modest traditional and electronic services, which are still at the beginning of the road and which are limited to some electronic plastic cards, The talking bank, the cellular bank, automated teller machines and express transfers.
Keywords: marketing; e-marketing; services; banking